2023
DOI: 10.7759/cureus.37704
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Enhancement in Fracture Healing: A Review of the Literature

Abstract: Bone healing constitutes a complex process involving cellular and pathophysiological mechanisms. Despite progress in osteosynthesis techniques, fracture union continues to be challenging. In some cases, it is not ultimately achieved or is delayed relative to the expected time resulting in economic and social outcomes for the patient and the health system. In addition to surgical treatment, biophysical methods have been developed to assist in fracture healing used in combination or individually. Biophysical sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Another non-invasive procedure is represented by biophysical stimulation that could be effectively applied in the treatment of delayed fracture healing in order to enhance bone regeneration [36]. De Francesco et al reported the use of biophysical stimulation (pulsed electromagnetic fields and capacitive coupling electric fields) in patients who underwent surgical fixation of hand phalanx with delayed union at 30 days from surgery [16].…”
mentioning
confidence: 99%
“…Another non-invasive procedure is represented by biophysical stimulation that could be effectively applied in the treatment of delayed fracture healing in order to enhance bone regeneration [36]. De Francesco et al reported the use of biophysical stimulation (pulsed electromagnetic fields and capacitive coupling electric fields) in patients who underwent surgical fixation of hand phalanx with delayed union at 30 days from surgery [16].…”
mentioning
confidence: 99%